(untitled) (Global Journal of Management and Business Research, 2013)
Cultural beliefs and philosophies are fundamental in shaping a society. Lately, there have been various discussions about the values of the African Ubuntu philosophy in many aspects as it relates to issues of human relationships, business ethics and corporate governance. As a governing African philosophy, the Ubuntu is inclusive in nature as it considers all members of the community (organisation) as one entity aiming at achieving one purpose. There have been assertions that the ultimate success of any organisation operating in an African environment is premised on this Ubuntu framework. This study aimed at establishing corporate governance approach as practiced by organisations within an African context. Thus, the paper analyses and reports on research findings pertaining to issues towards general business ethics and corporate governance approaches within an African context. The study results show that Africa’s socio-cultural framework that is premised on the Ubuntu philosophy resonates with general principles surrounding business ethics and corporate governance.